HEALING OF DIABETIC FOOT ULCER USING AUTOLOGOUS PERIPHERAL BLOODMONONUCLEAR STEM CELLS (STUDY CASE) - Basuki Supartono,; Prita Kusumaningsih; Muzayyana Sakinah, (Faculty of Agriculture Universitas Sebelas Maret, 2017)
Diabetic foot ulcer is the most dreaded complications of Diabetes Mellitus (DM), wound healing in patients with DM is a very important issue. Here, we report a case study of stem cell therapy on unhealed diabetic wound. The mononuclear stem cells (MNC) were isolated from patient's peripheral blood with Ficol gradient.Topically MNC stem cells administration on 47 years old female patient for 2 months, triggered the formation of granules in the cells of the surrounding wound. Eventually, wound were healed completely. In conclusions, MNC stem cells therapy healed end stage diabetic foot wounds, without surgery.